2022
DOI: 10.3390/app12136608
|View full text |Cite
|
Sign up to set email alerts
|

Age Prediction from Low Resolution, Dual-Energy X-ray Images Using Convolutional Neural Networks

Abstract: Age prediction from X-rays is an interesting research topic important for clinical applications such as biological maturity assessment. It is also useful in many other practical applications, including sports or forensic investigations for age verification purposes. Research on these issues is usually carried out using high-resolution X-ray scans of parts of the body, such as images of the hands or images of the chest. In this study, we used low-resolution, dual-energy, full-body X-ray absorptiometry images to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…For knees, an atlas was prepared by Pyle and Hoerr 26 . Janczyk et al considered low-dose, whole-body dual-energy x-ray scans of patients up to 19 years and obtained an MAE of 1.3 years, which is comparable to our results 27 .…”
Section: Discussionsupporting
confidence: 91%
“…For knees, an atlas was prepared by Pyle and Hoerr 26 . Janczyk et al considered low-dose, whole-body dual-energy x-ray scans of patients up to 19 years and obtained an MAE of 1.3 years, which is comparable to our results 27 .…”
Section: Discussionsupporting
confidence: 91%
“…The authors concluded that the two categories-low density followed by low volume have large association with major osteoporotic fractures. 2022) did experiments on low resolution full body DXA images to find the ages of persons [15]. The authors suggested pre-processing procedures and used partially pre-trained convolutional neural network algorithms.…”
Section: Whittier Et Al (2022) Applied Fuzzy C Means Clustering On Hi...mentioning
confidence: 99%
“…Since a bone age assessment is of great importance, this topic has been addressed in order to support physicians with an automated analysis of the data, making this task less labor intensive. In the literature, there are many approaches to address this problem, when analyzing X-ray images of hands [39][40][41][42][43][44][45], the chest [40,46], or whole-body images [47,48]. In the case of a fully automated deep learning approach, first the hand region was determined in the image using the U-Net network for semantic segmentation of the hand region, then the image registration was applied to allow for an easy determination of hand regions corresponding to each other between various images.…”
Section: Introductionmentioning
confidence: 99%